A preliminary cross-sectional study to investigate the presence of sarcopenic dysphagia in a Portuguese geriatric population - Portinha, Susana (2023)
The objective of this study is to investigate the presence of sarcopenia and the risk of oropharyngeal dysphagia (OD) in a geriatric population and to analyze the relationship between the factors associated with sarcopenic dysphagia. The cross-sectional study was carried out in two nursing homes. The presence of OD was screened using the gugging swallowing screen, and sarcopenia was assessed according to the European working group on sarcopenia in older people criteria. The sample (N=36; 23 women, 13 men) presents a mean age of 88.0±5.6, with 55.6% being at risk of OD, 52.8% with sarcopenia, and 36.1% with probable sarcopenic dysphagia. The score of the simple questionnaire to rapidly diagnose sarcopenia (SARC-F)≥4 was a significant predictor (odds ratio=9.0; confidence interval 95%=1.285-63.025) for the risk of having sarcopenic dysphagia. It was observed that sarcopenia was associated with higher odds of being at risk of OD. Also, an increase in age, poorly fitting prostheses, a higher level of dependence during activities of daily living, and a risk of malnutrition or malnourishment raised the potential of having probable sarcopenic dysphagia. We suggest including a speech and language therapist in the multidisciplinary geriatric teams to improve the prevention of sarcopenic dysphagia and to avoid its consequences.